Hydration kinetics of oil well cement in the temperature range between 5 and 30°C - Sun, Lijun; Pang, Xueyu; Yan, Haibing (Frontiers in Materials, 2022)
Modelling the transient temperature change of oil well cement during hydration is highly critical for offshore cementing projects related to natural gas hydrate. During this study, the heat release of oil well cement hydration in the temperature range between 5 °C and 30 °C was monitored by isothermal calorimetry. The influences of source of cement, water to cement (w/c) ratio, and CaCl2 accelerator on hydration kinetics were evaluated in great detail. Test results indicated that the temperature effect on cement hydration kinetics can be modelled by a scale factor derived from the apparent activation energy (Ea) of the cement. Ea showed strong dependence on temperature, moderate dependence on cement source and relatively little dependence on w/c ratio and CaCl2 addition. By combining with previous experimental data, a function correlating Ea and temperature in a wide temperature range (5-87 °C) was obtained.